Effectiveness of Cognitive Behavior Therapy in Improving Students’ Understanding of Bullying - Muslim Muslim; Neviyarni Neviyarni; Yeni Karneli (Global Econedu, 2019)
The aim of this study was to examine the effectiveness of counseling through cognitive behavioral therapy in improving students' understanding of bullying. This research is a Quasi-Experiment with the Time Series Design. The research subjects were 10 students, selected through Purposive Sampling techniques. The research instrument used therefore was the scale of understanding bullying with reliability of 0.900, and the data were analyzed using the Wilcoxon Signed Ranks Test through SPSS version 20.0. Based on the findings, counseling through cognitive behavioral therapy is highly effective in increasing students' understanding of bullying. This intervention aims to teach students a variety of skills to overcome their problems, thereby helping them to develop adaptive lifestyles.